The RNFA - Anesthetic Team Collaborative Connection - Spiece, Cheryl (Operating Room Nurses Association of Canada Journal, 2000)
A requirement of the Registered Nurse First Assistant (RNFA) Clinical Internship is to explore the RNFA collaborative role with the anaesthetic team in facilitating positive patient surgical outcomes.